Pengelolaan Bendung Konga sebagai Pemasok Air Bagi Pertanian di Desa Konga Kecamatan Titehena Kabupaten Flores Timur - Agnes Stefani Koten; Jacob Wadu; David Wilfrid Rihi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Sustainable reservoir management plays an essential role in ensuring the availability of irrigation water for agricultural development, particularly in regions that depend on surface water resources. This study aims to analyze the management of Konga Dam as a water supplier for agriculture in Konga Village, Titehena District, East Flores Regency based on four management dimensions: planning, utilization, controlling, and maintenance. This study employed a qualitative descriptive approach. Data were collected through field observations, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The findings indicate that the management of Konga Dam involves the Nusa Tenggara II River Basin Agency, the Public Works and Spatial Planning Office of East Nusa Tenggara Province, the Public Works Office of East Flores Regency, dam operational officers, water gate operators, Water User Farmers Associations, the village government, and local communities. Nevertheless, management effectiveness remains constrained by weak institutional coordination, unequal water distribution, limited supervision, and irregular infrastructure maintenance. The study concludes that sustainable management of Konga Dam requires stronger institutional governance, improved stakeholder coordination, and active community participation to ensure equitable and sustainable irrigation water distribution.